THE QUALITY OF INSTITUTIONS AND MULTINATIONAL CORPORATION: THE POLITICAL ECONOMY OF FOREIGN DIRECT INVESTMENT IN TURKEY - (:unkn) unknown (NOVA SCIENCE PUBLISHERS, INC, 2010)
The major focus of this chapter is on the relationship between political, social and economic institutions and Foreign Direct Investment in Turkey. For a decade, the relationship between institutions and Foreign Direct Investment has been receiving growing attention. The link between the quality of institutions and FDI in developing countries, especially in transition economies, has led scholars to focus on the quality of institutions as determinants of FDI in developing countries. In order to attract higher amounts of FDI, numerous developing countries have liberalized their investment environment since 1980. Turkey is not an exception. However, not all countries succeed at attracting FDI as they expected. The volume of FDI flows differ among the countries. One of the countries which did not succeed at attracting FDI as expected is Turkey. This chapter explores how social economic and political institutions help explain the low level of FDI flows into Turkey by offering a political economy approach and applying a questionnaire survey for the recent period.